МОТИВАЦІЯ ПЕРСОНАЛУ ОРГАНІЗАЦІЇ ДО ОБМІНУ ЗНАННЯМИ - Галина Анатоліївна Уткіна (International Journal of Innovative Technologies in Social Science, 2019)
The article deals with the key issues of the motivation specificity of implementing the intellectual activity of the personnel in an organization on the basis of knowledge economics. The construction of a mechanism of motivation in an organization that would stimulate extremely constructive behaviour that builds effective communication to achieve a consistent result of the team was proposed. The author studied the aspect of the goal implementation of "readiness for knowledge exchange" through the triad of procedures motive - motivation - an incentive to manage the knowledge of the organization, multiplication and transformation into a product of consumption. Based on the analysis of a number of theoretical sources, the goal is to identify and approve the meaning of “active intellectual organization” (“intellectual activity”) with the requirements of the production (of the society) based on competent economy and the possibility of its use as a measure of the intelligence formation of early transition to innovation. The further development is given to the definition of what constitutes “intellectual activity” by providing two main components of the factors that are defined, determining the meaning of the term - the mental ability of each person and the motivation of their activities, and a clear focus on what each of these factors is the only necessity, but is not sufficient, and only the two together are necessary and sufficient for the generation of intellectual activity. Axiomatic method, methods of theoretical generalization and comparison, analysis and synthesis in order to clarify the meaning of “motivation” are used in the process of the study.